2021
DOI: 10.3390/children8020096
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on the Adaptive Functioning, Behavioral Problems, and Repetitive Behaviors of Italian Children with Autism Spectrum Disorder: An Observational Study

Abstract: Children with autism spectrum disorder (ASD) and their families have represented a fragile population on which the extreme circumstances of the COVID-19 outbreak may have doubly impaired. Interruption of therapeutical interventions delivered in-person and routine disruption constituted some of the main challenges they had to face. This study investigated the impact of the COVID-19 lockdown on adaptive functioning, behavioral problems, and repetitive behaviors of children with ASD. In a sample of 85 Italian ASD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 30 publications
2
25
0
5
Order By: Relevance
“…Siracusano et al, [ 82 ] conducted an observational study on a sample of 85 children (aged 2–18 years) recruited from the clinical database of the Child Psychiatry Unit of the University of Rome Tor Vergata Hospital. Having diagnostic information and pre-confinement status by COVID-19, they develop an observation with measures such as the ABAS-II [ 83 ], RBS-R [ 84 ], and CBCL [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Siracusano et al, [ 82 ] conducted an observational study on a sample of 85 children (aged 2–18 years) recruited from the clinical database of the Child Psychiatry Unit of the University of Rome Tor Vergata Hospital. Having diagnostic information and pre-confinement status by COVID-19, they develop an observation with measures such as the ABAS-II [ 83 ], RBS-R [ 84 ], and CBCL [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Imposed home confinement, interruption of in-person interventions, school closure, remote working and job loss, represent extra difficulties for caregivers of children with disabilities belonging to several countries [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…With one exception, 20 the first wave of studies documenting the impact of the pandemic on ASD/NDD youth has consistently reported worsening behavioral and/or emotional problems, 12,16,17,49,50 ASD symptoms, 49,51 and/or sleep disruptions. 10,12,50,52 Our results underscore that solely focusing on group-level effects leads to an incomplete picture of the COVID-19 pandemic impact on ASD/NDD.…”
Section: Discussionmentioning
confidence: 99%
“…The initial adaptation was developed in English and then translated into five other languages and updated with rewordings in consultation with the larger AFAR network. The final version 0.5.1 of AFAR Parent/Caregiver Baseline Form (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) included 96 independent items, with 34 questions asked twice for Prior and Current timepoints; AFAR is freely available for use by other investigators. 29…”
Section: Survey Developmentmentioning
confidence: 99%
See 1 more Smart Citation